The Relationship between Celebrity Worship and Self-Esteem in the K-Pop Fan Community - Jannah, Miftahul; Niken Yuniar Sari; Aminatul Fitri (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
K-pop fans often experience celebrity worship which makes them tend to make social comparisons with celebrities they like. Social comparison is one of the factors that influences self-esteem, so that a person can evaluate themselves positively or negatively. This research aims to determine the relationship between celebrity worship and self-esteem in the K-pop fan community. This research is a cross sectional study, with a purposive sampling design. This research was conducted on 94 K-pop fans in Pekanbaru City. The questionnaires used were the Celebrity Attitude Scale (CAS) and the Rosenberg Self-Esteem Scale (RSES). The statistical test used is the Chi Square test with the alternative Continuity Correction test. As many as 61.1% of respondents experienced low celebrity worship and as many as 57.4% of respondents had high self-esteem. Statistical analysis shows p value = 0.039 (p value < α = 0.05). This research shows that there is a relationship between celebrity worship and self-esteem. However, more in-depth research is still needed regarding other factors that influence self-esteem which were not examined in this study.